2022
DOI: 10.21203/rs.3.rs-2171149/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction of promyelocytic leukemia zinc finger protein by miR-200c-3p restores sensitivity to anti-androgen therapy in androgen-refractory prostate cancer and inhibits the cancer progression via down-regulation of integrin α3β4

Abstract: Purpose Androgen-refractory prostate cancer (ARPC) is one of the aggressive human cancers with metastatic capacity and resistance to androgen deprivation therapy (ADT). The present study investigated the genes responsible for ARPC progression and ADT resistance, and their regulatory mechanisms. Methods Transcriptome analysis, co-immunoprecipitation, confocal microscopy, and FACS analysis were performed to determine differentially-expressed genes, integrin α3β4 heterodimer, and cancer stem cell (CSC) populati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…The present study demonstrates that IL-8 is the most highly expressed cytokine in ARPC cells, confirming our previous transcriptome analysis of hormone-responsive and hormone-refractory PC cells ( Dahal et al ., 2022 ). Previously, it was reported that IL-8 is a tumor-intrinsic factor that contributes to PC progression as well as resistance to ADT and immune checkpoint inhibitors ( Lopez-Bujanda et al ., 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrates that IL-8 is the most highly expressed cytokine in ARPC cells, confirming our previous transcriptome analysis of hormone-responsive and hormone-refractory PC cells ( Dahal et al ., 2022 ). Previously, it was reported that IL-8 is a tumor-intrinsic factor that contributes to PC progression as well as resistance to ADT and immune checkpoint inhibitors ( Lopez-Bujanda et al ., 2021 ).…”
Section: Discussionsupporting
confidence: 92%